CNS metastasis from malignant uveal melanoma: a clinical and histopathological characterisation. Issue 5 (17th December 2008) - Holfort, S K; Lindegaard, J; Isager, P; Prause, J U; Heegaard, S
Abstract : Aim: To characterise uveal melanoma that has metastasised to the central nervous system (CNS). Methods: Review of 2365 patients constituting all patients diagnosed as having primary uveal melanoma in Denmark during the period 1943–1997. All patients with malignant uveal melanoma and metastasis to the CNS were identified. For each patient, clinical and histopathological data were gathered. Results: Sixteen patients with CNS metastasis were identified. The median age was 58 years. The majority of CNS metastases were located in the frontal and parietal lobes. Eleven patients had widespread metastases. Five patients had exclusively metastasis to the CNS. The average time from diagnosis of primary tumour to symptoms of CNS metastasis was 91 months. The average time from the initial CNS symptoms to death was 20 months. All tumours were composed of either mixed or spindle cells. The average largest basal diameter of the primary tumours was 12 mm. One tumour was a ring melanoma. The majority of tumours had a ruptured Bruch membrane. Retinal invasion was observed in 36% of tumours. No specimen had optic nerve invasion. Scleral invasion was pronounced in 36% of cases, and extrascleral extension was observed in two cases (14%). The amount of tumour infiltrating lymphocytes was pronounced in three cases (23%). Conclusion: The proportion of uveal melanoma patients having CNS metastasis was 0.7%. Eleven patients had multiple organ metastases, and the average time from the initial CNS symptoms to death was 8 months. Five patients had metastasis to the CNS solely, and the average time from the initial CNS symptoms to death was 57 months.